Ginger Rhizome Extract (Zingiber officinale) as an Alternative Bioinsecticide Against The Mortality of German Cockroach (Blattella germanica): Indonesia - Susanto, Inneke Kusumawati; Susilowati, Rina Priastini; Hidajat, Joshua Jean Michael (Universitas Kristen Krida Wacana, 2024)
Cockroach is one of the types of insects that exists everywhere. Cockroach can live in a lot of places, such as the gutter, the trash, and even in the bathroom. Cockroach is one of the agents that is responsible for the spreading of diseases such as diarrhea, dysentery and cholera in children. In Indonesia, there exists a lot of different types of cockroach, one of it is the German Cockroach or Blattella germanica L., and the cockroach problem in Indonesia is mainly handled by using chemicals insecticides, this happens because there’s a lot and its commonly found in a lot of places. Pyrethroid based chemicals insecticides are one of the most common chemical insecticides used by the public. These chemical insecticides have various kinds of adverse effects because they leave residues that can be inhaled by humans and also consumed by humans through food products. Some of the effects of chemical insecticides are diseases of the liver, kidneys, and also problems with the central nervous system. Therefore, an alternative solution is needed in dealing with the cockroach problems in Indonesia, namely Bioinsecticides. Bioinsecticides are insecticides made using natural ingredients without the addition of chemical substances. Ginger is one of the spices that can be found anywhere, in ginger there are compounds called flavonoids, and these compounds can be used as bioinsecticides. Bioinsecticides are made by taking the ginger extract then putting the extract into a spray bottle according to the dose using a pasteur pipette.